Efek Larutan Kopi Robusta terhadap Kekuatan Tekan Resin Komposit Nanofiller - Endang Sasi Andari; Erawati Wulandari; Dwi Merry Ch. Robin (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2014)
Nanofilled composite resin is a restorative material that can withstand mastication force in the posterior region. The compressive strength of composite resin is influenced by beverages consumption. Robusta coffee is the most consumed beverages by Indonesian society. It is an acidic-beverage that containing chlorogenic acid, therefore coffee solution can be expected to increase water absorption and solubility of restorative materials. This study was aimed to know the effect of robusta coffee solution to the compressive strength of nanofilled composite resin. Samples were 64 discs nanofilled composite resin, diameter 5 mm and thickness 2 mm. Samples were divided into 4 control group (immersed in aquadest) and 4 treatment group (immersed in robusta coffee solution). Every group contained of 8 samples and immersed for 1, 3, 5, and 7 days. Compressive strength was tested by using Universal Testing Machine. It showed average compressive strength value of control group was higher than treatment group. It increased on 3rd and 5th day then decreased on 7th day. Compressive strength value in teratment group approximately decreased on 3rd, 5th, and 7th day. Nonparametric statisic analysis Kruskal-Wallis and Mann-Whitney showed no difference among control group and treatment group (p>0,05) according to immersion time (days). It concluded that robusta coffee solution decrease the compressive strength of nanofilled composite resin.